PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI SEKOLAH MENENGAH ATAS KOTA BANDA ACEH - Marlisa, Rika; Fuadi, Raida; Adria, Agus (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
Developed countries are often characterized by several factors, one of which is education. Education is a state effort to develop physical and spiritual potentials in accordance with societal values. In Indonesia, the government supports education through programs like School Operational Assistance (BOS) to help with education costs as outlined in the Constitution of the Republic of Indonesia Number 18 of 2022 concerning Funding of Education Expenses. According to the 2003 National Education System Law, the management of education funds must follow the principles of fairness, efficiency, transparency, and public accountability. Therefore, both the government and the community must manage education funds transparently and accountable so the public can see the utilization of school funds. This study aims to determine the effect of accountability and transparency on the BOS funds management in senior high schools in Banda Aceh City. This quantitative research involved all 17 high schools in Banda Aceh City, using a saturated sampling technique through questionnaires. The results indicate that accountability significantly influences the management of BOS funds in these schools and that the implementation has been effective.